Juvenile Delinquency and Adult Crime, 1948-1977 (Racine, Wisconsin): Three Birth Cohorts - Shannon, Lyle W. ([Verlag nicht ermittelbar], 1984)
This data collection contains information on juvenile delinquency and adult crime for three birth cohorts born in 1942, 1949, and 1955 in Racine, Wisconsin. These individual-level data are organized into three basic types: police contact data for the three cohorts, interview and contact data for the 1942 and 1949 cohorts, and contact data classified by age for all three cohorts. The police contact data include information on the type and frequency of police contacts by individual as well as the location, date, and number of the first contact. The interview datasets contain information on police contacts and a number of variables measured during personal interviews with the 1942 and 1949 cohorts. The interview variables include retrospective measures of the respondents' attitudes toward the police and a variety of other variables such as socioeconomic status and age at marriage. The age-by-age datasets provide juvenile court and police contact data classified by age.